The Significance of 'Nila' In Malay Foundation Myths: A Study of Sri Nila Pahlawan - Fytullah Hamzah; Ahmad Azaini bin Abdul Manaf (ITB Journal Publisher, LPPM ITB, 2019)
This article examines the true significance of nila (blue) in the Malay literature from an ocular point of view. The origins of Malay foundation myths as written in the Malay Annals by Tun Sri Lanang, which contain a detailed description of the ancestry of Raja Iskandar Zulkarnain, Sang Sapurba, his miraculous appearance at Bukit Seguntang and introduces the renowned covenant with Demang Lebar Daun, the ruler of Palembang. This study outlines the appearance of nila in ancient texts (Sri Nila Pahlawan, Sang Nila Utama, Tuan Putri Nila Panjadi). A visual and textual approach was employed to investigate the importance of nila in ancient Malay myths and the determination of its usage in the narratives. Each description was examined and drawn in detail from the aspects of depictions, compared to other texts on the same point and degrees in the Malay world. The aim of this inquiry was to separate the history part from the mythical part and to determine the meaning of the nila designation that occurs in multiple accounts throughout the literature. As a conclusion, according to the usage of nilain the Malay Annals it can be seen as a name to represent the divine or supreme status of the ruling royal family.